DEFINITION OF CONTROL SIGNALS FOR PERFORMING CERTAIN GATES BY KERR CELLS IN A NONLINEAR RESONATOR - Karayan, H.S.; Chibukhchyan, A.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
Considered the effects of external optical signals on the entangled states of the Fock of Kerr qubits in a nonlinear resonator. The necessary time dependence of the Hamiltonian for the realization of negation, Hadamard and controlled negation operators for the algebra of quantum logic have been found.
Keywords: helix–coil transition, biphasic denaturation, multiple binding